Virtual Memory: Historical experiences with augmented reality: Memória Virtual: Experiências históricas com realidade aumentada (Revista de História da UEG (REVHIST), 2024)
This article addresses and includes potential pedagogical practices within the "Virtual Memory" project carried out in the context of "Multifest" in 2019 by the Multimedia and Audiovisual Production program at UDLA. It is worth noting that this is a narrative-driven account, not merely aiming to showcase a product but rather aiming to present pedagogical possibilities that can be implemented, while also serving as a complement in innovative educational spaces through the use of these tools and practices in the classroom. Therefore, through the utilization of new technologies and cutting-edge tools, this process has placed significant emphasis and responsibility on historically indigenous characters within real, digital, and educational environments with the aim of imparting a small yet crucial part of our culture and history through the use of technology.Keywords: Augmented Reality. Audiovisual. Multimedia. Aboriginal women. Ecuador.